2010
DOI: 10.1016/j.dsr2.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Diel and ontogenetic variations in vertical distributions of large grazing copepods during the spring phytoplankton bloom in the Oyashio region

Abstract: 11Short-term changes in vertical distributions of copepods during the spring 12 phytoplankton bloom were analyzed based on day and night vertically stratified 13 sampling (9 strata between 0-1000 m) with a fine-mesh (60 µm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In contrast to C. pacificus, during springsummer E. californicus lives somewhat deeper in the water column, just below the mixed layer (Ohman et al, 1998). This vertical distribution recalls that of its congener Eucalanus bungii in the Subarctic Pacific, which, together with Neocalanus cristatus, resides somewhat deeper than other particle-grazing copepods (Neocalanus plumchrus and Neocalanus flemingeri, Mackas et al, 1993), although E. bungii adults can occur near the surface in spring in the Oyashio region (Yamaguchi et al, 2010). An expected consequence of residence below the mixed layer in the California Current System is that the phytoplankton prey available to E. californicus would likely come from a somewhat deeper depth than those commonly encountered by C. pacificus (or would arrive in the form of sinking particles).…”
Section: Temporal Changesmentioning
confidence: 78%
“…In contrast to C. pacificus, during springsummer E. californicus lives somewhat deeper in the water column, just below the mixed layer (Ohman et al, 1998). This vertical distribution recalls that of its congener Eucalanus bungii in the Subarctic Pacific, which, together with Neocalanus cristatus, resides somewhat deeper than other particle-grazing copepods (Neocalanus plumchrus and Neocalanus flemingeri, Mackas et al, 1993), although E. bungii adults can occur near the surface in spring in the Oyashio region (Yamaguchi et al, 2010). An expected consequence of residence below the mixed layer in the California Current System is that the phytoplankton prey available to E. californicus would likely come from a somewhat deeper depth than those commonly encountered by C. pacificus (or would arrive in the form of sinking particles).…”
Section: Temporal Changesmentioning
confidence: 78%
“…In the high latitudes, some observations have found that DVM may stop during periods of midnight sun and polar night (Blachowiak‐Samolyk et al, ; Falkenhaug et al, ; Fischer & Visbeck, ) although this remains controversial (Berge et al, ; Cottier et al, ). During wintertime, many species perform ontogenetic seasonal migrations and reside in the mesopelagic domain (Shimode et al, ; Yamaguchi et al, ). Thus, overlaps might exist in reality between the three modeled communities in contrast to what is assumed in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Although Kurita and Sugisaki (2004) and Sugisaki and Kurita (2004) reported gut content weight to be higher at dusk, the present study indicated that active feeding time was different by prey taxa and/or ocean area. Because the diurnal vertical migration is unclear or small in Neocalanus copepods (Mackas et al., 1993; Yamaguchi et al., 2010), Pacific saury might be able to access these preys through the day. Thus, these time‐of‐day differences might be also linked to behavior and feeding activity in Pacific saury.…”
Section: Discussionmentioning
confidence: 99%